Process improvement applying the DMAIC methodology in a plastic injection plant - JULCARIMA, SEBASTIAN ARIAN; ARAGON, LUCY GABRIELA (LACCEI, 2024)
In a global plastics market in constant growth and competitiveness, continuous process improvement has become essential to guarantee quality, efficiency and customer satisfaction in the plastic injection industry. This study focuses on the application of the DMAIC methodology to address the challenges in the plastic cap manufacturing process in a Peruvian company with more than 25 injection machines. The analysis begins by identifying key issues, such as variability in raw material quality and inconsistency in plug dimensions, using tools such as QFD matrix and statistical analysis. The magnitude of these problems is then measured and relevant data is collected, followed by an in-depth analysis to identify root causes using tools such as the Ishikawa diagram and ANOVA R&R. Based on these conclusions, improvements are proposed, such as staff training and standardization of raw material acceptance criteria, which are implemented and remeasured to evaluate their effectiveness. Finally, control indicators are established and recommendations are made for quality management, including periodic audits and the promotion of a culture of continuous improvement. This systematic, data-driven approach has proven effective in addressing quality issues, reducing process variability, and improving market competitiveness. The results and recommendations derived from this study provide valuable guidance for quality management and continuous improvement in the plastic injection plant, highlighting the importance of a collaborative and customer-focused approach to ensure long-term success in the industry.